The Influence of Leadership Style and Work Discipline on Employee Performance at PT. Komunitas Anak Bangsa Jakarta - I Gede Marendra; Chotamul Fajri; Retno Japanis Permatasari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of leadership style and work discipline on employee performance at PT. Komunitas Anak Bangsa Jakarta. The sample in the study was 69 respondents using quantitative methods. This research technique uses data instrument tests, classical assumption tests, descriptive analysis, regression analysis, correlation and determination. The results processed in this research on the leadership style variable have a significant influence, there are employee performance variables with a value of 0.014 < 0.05. The work discipline variable has a significant effect on the employee performance variable with a value of 0.001 < 0.05. Meanwhile, simultaneously the leadership style variable and the work discipline variable have a significant effect on the employee performance variable with a value of 0.001 < 0.05.